Pengaruh Arus Kas Operasi, Penjualan dan Likuiditas Terhadap Profitabilitas Pada PT Kencana Permata Nusantara Periode 2014-2018 - Ferdinand Napitupulu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
The purpose of this study was to determine and analyze the effect of operating cash flow, sales and liquidity on profitability at PT Kencana Permata Nusantara for the 2014-2018 period. The method used in this research is descriptive analysis method by describing or describing the data that has been collected as it is without intending to make conclusions that apply to the public or generalization. Data analysis method used is multiple linear regression using SPSS software. The results showed that operating cash flow, sales and liquidity simultaneously had a positive and significant effect on profitability at PT Kencana Permata Nusantara for the 2014-2018 period. In the coefficient of determination R2 Adjusted value obtained by 59% means that the variable variations in operating cash flow, sales and liquidity can explain its effect on profitability while the remaining 41% is a variation of other variables not explained in this study such as capital, income, etc. Operating cash flow partially has a positive and significant effect on profitability at PT Kencana Permata Nusantara for the 2014-2018 period. This shows that operating cash flow has a positive effect in theory as well as a significant significant effect in increasing profitability at PT Kencana Permata Nusantara for the 2014-2018 period. Partial sales have a positive and significant effect on profitability at PT Kencana Permata Nusantara for the 2014-2018 period. This shows that sales have a positive effect in theory and significantly influence significantly in increasing profitability at PT Kencana Permata Nusantara for the 2014-2018 period. Liquidity partially has a negative and not significant effect on profitability at PT Kencana Permata Nusantara for the 2014-2018 period. This shows that Liquidity has a negative and not significant effect in increasing the Profitability of PT Kencana Permata Nusantara for the 2014-2018 Period